An Enhanced Incremental Nonlinear Dynamic Inversion Control Strategy for Advanced Unmanned Aircraft Systems - Maryam Taherinezhad; Alejandro Ramirez-Serrano (Aerospace, 2023)
A cascade control architecture was proposed for the control of advanced unmanned aerial vehicles targeted for operation inside confined hazardous spaces. The aircraft of interest is a highly maneuverable system presenting highly coupled dynamics, enabling it to perform unique flight maneuvers that no other aircraft can. To deal with the complexities inherent to such an aircraft, a novel nonlinear control architecture was proposed. Two outer loop NDI controllers and an inner loop INDI controller were employed for position/velocity and attitude/rotation rate control, respectively. These controllers assist each other, enabling them to decouple the aircraft dynamics while coping with complex external disturbances. The obtained results demonstrate an effective control of the targeted aircraft system to accurately track complex flight maneuvers.